Histamine and motivation - Torrealba, Fernando; Riveros, Maria Eugenia; Contreras, Marco; Valdes, Jose Luis (Frontiers in Systems Neuroscience, 2012)
Brain histamine may influence a variety of different behavioral and physiological functions, but its responsibility in waking up has casted a long shadow on other important functions of this neurotransmitter. Here we review evidence indicating a central role of brain histamine in motivation, emphasizing its differential involvement in the appetitive and consummatory phases of motivated behaviors. We discuss the inputs that control the histaminergic neurons of the tuberomamillary nucleus of the hypothalamus, which determine the distinct role of these neurons in appetitive behavior, sleep/wake cycles and in food anticipatory activity. We review evidence supporting a dysfunction of histamine neurons and its cortical input in certain forms of decreased motivation (apathy). We finally discuss the relationship between the histamine system and drug addiction as a dysfunction of motivation.